2013
DOI: 10.1007/s12560-013-9121-5
|View full text |Cite
|
Sign up to set email alerts
|

GIV Noroviruses in Wastewaters and in Stool Specimens from Hospitalized Patients

Abstract: Noroviruses (NoVs) are important human pathogens associated with foodborne and waterborne gastroenteritis. These viruses are genetically highly heterogeneous, with more than forty genotypes within three genogroups (GI, GII, and GIV) identified in humans. However, the vast majority of human infections are associated with variants of a unique genotype, GII.4. Aside from these NoV strains of epidemiological relevance, NoV strains of genogroup GIV (Alphatron-like) are reported in a sporadic fashion and their overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Our study demonstrated a low prevalence of NoV GIV.1 as described in other studies [6,22,27,28]. Both the NoV GIV.1-positive patients were hospitalized with gastroenteritis in July of 2011 from Lulong County.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our study demonstrated a low prevalence of NoV GIV.1 as described in other studies [6,22,27,28]. Both the NoV GIV.1-positive patients were hospitalized with gastroenteritis in July of 2011 from Lulong County.…”
Section: Similar and Contrasting Cases In The Literature And Discussionsupporting
confidence: 76%
“…Human GIV.1 NoVs were first identified from sporadic cases of gastroenteritis [21]. From then on, they were occasionally detected in NoVs routine screenings of clinical and environmental samples [4][5][6][7]22]. Interestingly, in animals, GIV.2 NoVs were also detected [9,23,24].…”
Section: Similar and Contrasting Cases In The Literature And Discussionmentioning
confidence: 99%
“…Before concentration, all samples were artificially contaminated with a murine norovirus (MNV‐1) used as sample process control, to calculate viral recovery efficiency (by quantitative PCR) and check for potential inhibitors (by qualitative PCR) as previously described (Muscillo et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The overall recovery efficiency was calculated by dividing the number of genome copies in the sample by the number of genome copies in the original virus preparation used for spiking samples. The primers and probes for the TaqMan RT-PCR assay were previously designed (Muscillo et al 2013). Real-Time PCRs were carried out in a MiniOpticon Real-Time PCR System (Bio Rad) with CFX Manager software control.…”
Section: Quantitative Real-time Pcr For Mnv-1mentioning
confidence: 99%